IMPROVED KNOWLEDGE OF YOUNG GIRL ABOUT MENARCHE IN THE RANGKAH KIDUL ELEMENTARY SCHOOL, RANGKAH KIDUL VILLAGE, SIDOARJO SUB-DISTRICT, SIDOARJO DISTRICT, EAST JAVA PROVINCE - Riesmiyatiningdyah Riesmiyatiningdyah; Connie Wahyu Wijianti; Sinta Nuriyah; Lidia Getreda Masela; Dwi Setyowati Rahayu; Muhammad Mughni Maulana; Meita Yusti Anugrah Sari; Arina Rifatur Rizqya (Community Service Journal of Indonesia, 2019)
Improved knowledge of young girl about menarche in the Rangkah Kidul Elementary School, Rangkah Kidul Village, Sidoarjo Sub-District, Sidoarjo District, East Java Province is a form of education in the form of counseling aimed at growing and increasing knowledge related to menarche. The activity was held on November 27, 2018 at the Rangkah Kidul Elementary School, Rangkah Kidul Village, Sidoarjo Sub-District, Sidoarjo District, East Java Province. With the goal is a 5th grade student at the Rangkah Kidul Elementary School, Rangkah Kidul Village, Sidoarjo Sub-District, Sidoarjo District, East Java Province. Before the implementation of these activities, there is a process of preparing activities for 3 weeks before the activities are carried out, starting from the selection of health counseling materials to the submission of permits to related parties. As an evaluation, the event was attended by 18 participants who were 5th grade students, participants took part in the activity enthusiastically and conductively, the activities could be carried out on time smoothly. Keywords: Menarche, adolescent, health promotion, elementary school.